To identify the solution for the system of equations based on Jian's table, we need to look for the x-value(s) for which the y-values from both equations are equal.
From the table:
-
For \( x = 0 \):
- \( y = 2(0) - 5 = -5 \)
- \( y = 0 - 3 = -3 \)
-
For \( x = 1 \):
- \( y = 2(1) - 5 = -3 \)
- \( y = 1 - 3 = -2 \)
-
For \( x = 2 \):
- \( y = 2(2) - 5 = -1 \)
- \( y = 2 - 3 = -1 \)
-
For \( x = 3 \):
- \( y = 2(3) - 5 = 1 \)
- \( y = 3 - 3 = 0 \)
We see that when \( x = 2 \), both equations yield \( y = -1 \).
Therefore, the solution to the system of equations is \( (2, -1) \).
So the correct response is:
(2,−1)